PENGARUH PENGGUNAAN METODE JARIMATIKA TERHADAP KETERAMPILAN BERHITUNG SISWA KELAS II SD NEGERI 6 MENTENG KOTA PALANGKA RAYA TAHUN AJARAN 2023/2024: PENGARUH PENGGUNAAN METODE JARIMATIKA TERHADAP KETERAMPILAN BERHITUNG SISWA KELAS II SD NEGERI 6 MENTENG KOTA PALANGKA RAYA TAHUN AJARAN 2023/2024 - preti, Preti; Nyoto; Widya Permata, Dilla (PGSD FKIP UPR, 2025)
One of the basic mathematics skills that students need to master is counting skills. Students' numeracy skills tend to be hampered, one of them has difficulty calculating so that their mathematics learning achievement is not optimal. Based on these problems, efforts to improve learning are needed. The finger method can be used as an alternative method for learning to count for students because it utilizes the media of the fingers (touch/tactical sense) in its application. This research was conducted using a quantitative approach. The research subjects consisted of 22 students at SD Negeri 6 Menteng, all of whom were included in the experimental group. This research method uses quasi-experiment (Quasi Experimental Desing). Data collection techniques through observation, interviews, tests and documentation. The research instrument uses validity and reliability tests. Data analysis uses normality, homogeneity and hypothesis testing analysis techniques. The results of this research show that the t-test uses the independent sample t-test formula, so that the tcount of 19.307 is greater than the ttable, namely 2.018 at the significance level a = 0.05. So it can be concluded that Ha is accepted and Ho is rejected or that there is an influence of using the Jarimatika method on the numeracy skills of class II students at SDN 6 Menteng, Palangka Raya City in 2023/2024.